Online Travel Agent Marketing Strategy Through Social Interaction During the Pandemic COVID-19 - Ramadani, Mita Putri; Ambarwati, Rita; Hariasih, Misti (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
The Covid-19 pandemic has had such a devastating impact on Online Travel Agents such as Traveloka that it has made it to the lowest phase it has ever experienced. There are government regulations that limit people's social interactions so that various strategies are carried out, from using promos or utilizing application features. The purpose of this research is to find out whether the difference in social interaction between Traveloka users before and during the Covid pandemic was significant enough to evaluate Traveloka's marketing strategy. Decreased application usage, ticket rescheduling requests to refund requests which are currently Traveloka's problems. This research is qualitative research that uses the Social Network Analysis (SNA) method using the Twitter application assisted by the Jupyter Anaconda application, Google collab, and Ghepi. From the visualization of this study, the results obtained from 3 research focuses had significant differences from social interactions using Traveloka during the pandemic. From promos that experienced a decrease in interaction during the pandemic, Traveloka Xperience experienced an increase in feature usage, and the ticket feature experienced a decline in social interaction. So that Traveloka is expected to improve the company's strategy to survive during the pandemic.